Layered composite hydroxide modified zirconia material, and preparation method and application thereof

CN122644042APending Publication Date: 2026-08-28FUJIAN HENGSHEN CHEMICAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610780103.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-02
Publication Date
2026-08-28

AI Technical Summary

Technical Problem

这些脱落的Ru纳米颗粒由于粒径极小,在反应液后续的沉降分离过程中,同时受到重力、浮力、范德华力等多种复杂作用力的影响,且在流体环境中表现出强烈的布朗运动,因此通过常规物理方法难以有效沉降,极易漂浮聚集在油水界面层,并随物料排出而流失,最终导致昂贵的贵金属Ru损失,增加生产成本

Benefits of technology

显著的Ru沉降效果与低流失率:本发明通过对氧化锆分散剂进行层状复合氢氧化物的表面改性,提高了其亲水性和表面正电性,增强了对脱落的Ru纳米颗粒的吸附捕捉能力。实验数据表明,使用本发明的ZnAl-LDHs@ZrO2材料作为分散剂,Ru的流失率可从使用纯ZrO2的7.7%大幅降低至1.4%,同时催化剂的沉降速率也得到提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122644042A_ABST
    Figure CN122644042A_ABST
Patent Text Reader

Abstract

The application provides a layered composite hydroxide modified zirconium oxide material and a preparation method and application thereof, and belongs to the field of catalyst auxiliary materials. The material is composed of layered composite hydroxide and zirconium oxide, the layer plate of the layered composite hydroxide is composed of divalent metal cations and trivalent metal cations, and the modification amount is 1 / 30-1 / 200 of the mass of zirconium oxide. The material is prepared by combining a colloidal method and an electrostatic self-assembly method, can significantly improve the hydrophilicity of zirconium oxide and the adsorption capacity of ruthenium nanoparticles, and is applied to a benzene partial hydrogenation reaction system for preparing cyclohexene. The material can effectively promote the settlement of noble metal Ru nanoparticles under the premise of maintaining the reaction activity and selectivity, and significantly reduces the loss of Ru. Experiments show that the Ru loss rate can be as low as 1.4% by using the material, which is significantly improved compared with traditional zirconium oxide materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst auxiliary materials technology, specifically relating to a layered composite hydroxide modified zirconium oxide material, its preparation method, and its application in promoting the sedimentation of noble metal Ru nanoparticles in the partial hydrogenation of benzene to cyclohexene. Background Technology

[0002] Cyclohexene is a key intermediate in the production of chemical products such as nylon 6 and nylon 66. Currently, the mainstream industrial method for producing cyclohexene is the partial hydrogenation of benzene. This process generally uses a heterogeneous catalytic reaction system with ruthenium (Ru) as the main catalyst, zinc sulfate as the co-catalyst, and zirconium oxide as the dispersant.

[0003] The partial hydrogenation of benzene to cyclohexene is a gas-liquid-solid multiphase reaction carried out in a continuous stirred tank reactor. The strong shear force generated by the high-speed rotating impeller causes Ru catalyst particles to break down and detach from the surface of the zirconia dispersant, forming fine Ru nanoparticles. Due to their extremely small size, these detached Ru nanoparticles are simultaneously affected by multiple complex forces such as gravity, buoyancy, and van der Waals forces during the subsequent sedimentation and separation process of the reaction liquid. They also exhibit strong Brownian motion in the fluid environment, making them difficult to settle effectively using conventional physical methods. They easily float and accumulate at the oil-water interface and are lost with the discharged material, ultimately resulting in the loss of the expensive precious metal Ru and increasing production costs.

[0004] In existing technologies, conventional methods for promoting particle sedimentation, such as adding flocculants or surfactants, can agglomerate Ru nanoparticles, but they also disrupt the original structure of the catalyst, severely negatively impacting the selectivity and activity of the partial hydrogenation reaction of benzene, making them unsuitable for this system. Therefore, there is an urgent need to develop a novel material that can effectively promote the sedimentation of Ru nanoparticles and reduce their loss without affecting the catalytic reaction performance. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a layered composite hydroxide-modified zirconium oxide material, its preparation method and application. This material is used in the reaction system of partial hydrogenation of benzene to cyclohexene. It can significantly promote the sedimentation of Ru nanoparticles and greatly reduce the loss rate of Ru while maintaining high reactivity and selectivity.

[0006] This invention is implemented as follows: A layered composite hydroxide-modified zirconia material, the material being composed of a layered composite hydroxide and zirconia; the layers of the layered composite hydroxide are composed of divalent metal cations and trivalent metal cations, and the layers are positively charged; the divalent metal cations are selected from at least one of Zn²⁺, Mg²⁺, Co²⁺, Ni²⁺, and Cu²⁺, and the trivalent metal cations are selected from at least one of Al³⁺, Fe³⁺, Co³⁺, Mn³⁺, and Ga³⁺; the modification amount of the layered composite hydroxide is 1 / 30 to 1 / 200 of the mass of zirconia.

[0007] Furthermore, in the layered composite hydroxide, the molar ratio of divalent metal cations to trivalent metal cations is (2~16):1.

[0008] Furthermore, the layered composite hydroxide is a zinc-aluminum composite hydroxide (ZnAl-LDHs), and the zirconium oxide is a monoclinic zirconium oxide (ZrO2).

[0009] Furthermore, the material exhibits a first strong diffraction peak on the (003) crystal plane of the layered composite hydroxide at a 2θ angle of 10-15 degrees, and a second strong diffraction peak on the (006) crystal plane at a 2θ angle of 20-25 degrees, with the height ratio of the first strong peak to the second strong peak being (1-3):1.

[0010] Furthermore, the preparation method of the layered composite hydroxide-modified zirconium oxide material includes the following steps: S1. Preparation of layered composite hydroxide colloid: According to the molar ratio of divalent metal ions to trivalent metal ions of (2~16):1, weigh the corresponding divalent metal salts and trivalent metal salts and dissolve them in deionized water to prepare solution A; dissolve sodium hydroxide in deionized water to prepare solution B; dissolve sodium carbonate in deionized water to prepare solution C; under stirring conditions, slowly add solutions A and B dropwise to a reactor containing solution C, controlling the pH of the system to 8.0±2.0; after solution A has been added, stop adding solution B, and age the resulting colloid at 40°C~90°C for 3~12 hours to obtain a layered composite hydroxide colloid; S2. Preparation of layered composite hydroxide-modified zirconia materials: Zirconia is added to the layered composite hydroxide colloid obtained in step S1, and the mixture is stirred vigorously for 3 to 12 hours to allow it to fully adsorb and self-assemble. The resulting precipitate is filtered, washed, and dried to obtain the layered composite hydroxide modified zirconium oxide material.

[0011] Further, in step S1, the ratio of the total molar amount of the divalent and trivalent metal ions to the molar amount of sodium hydroxide is 1:(1~5); the molar concentration of solution B is 0.01~0.1 mol / L.

[0012] Further, in step S1, the ratio of the total molar amount of divalent and trivalent metal ions to the molar amount of sodium carbonate is (2~16):1; the molar concentration of solution C is 0.01~0.1 mol / L.

[0013] Further, in step S2, the amount of zirconium oxide added is 30 to 200 times the amount of layered composite hydroxide modification, and the resulting precipitate is dried at 40°C to 80°C for 4 to 16 hours.

[0014] Furthermore, in the application of the layered composite hydroxide-modified zirconium oxide material in the reaction system of benzene partial hydrogenation to cyclohexene, the material is used as a catalyst dispersant, and the amount of dispersant is 5 to 10 times that of the catalyst, so as to promote the sedimentation of noble metal Ru nanoparticles in the reaction system and reduce Ru loss.

[0015] Furthermore, the application includes using the layered composite hydroxide-modified zirconium oxide material together with a Ru catalyst for the partial hydrogenation of benzene to cyclohexene, with a sedimentation rate of 6~8 cm³ / (min·gcat) for the catalyst system.

[0016] The present invention has the following advantages: Significant Ru sedimentation effect and low loss rate: This invention improves the hydrophilicity and surface positive charge of the zirconium oxide dispersant by surface modification with layered composite hydroxides, thereby enhancing its adsorption and capture capacity for detached Ru nanoparticles. Experimental data show that using the ZnAl-LDHs@ZrO2 material of this invention as a dispersant, the Ru loss rate can be significantly reduced from 7.7% using pure ZrO2 to 1.4%, while the catalyst sedimentation rate is also improved.

[0017] No negative impact on catalytic performance: The material of this invention promotes the sedimentation of Ru nanoparticles without damaging the catalyst structure or introducing harmful substances. Laboratory small-scale evaluation shows that the benzene conversion rate can still be maintained above 40%, and the cyclohexene selectivity is around 80%, without causing any negative impact on the main reaction.

[0018] The preparation method is stable and reliable: the preparation method of this invention ensures uniform and stable modification of the layered composite hydroxide on the zirconium oxide surface through key steps such as colloidal aging and electrostatic self-assembly. This process demonstrates good scalability and reproducibility from small-scale to kilogram-scale pilot-scale tests, showing promising prospects for industrial application.

[0019] In summary, this invention is the first to apply layered composite hydroxide-modified zirconium oxide material to a benzene partial hydrogenation system, utilizing the material's unique structure and surface properties to solve the problem of Ru nanoparticle loss, providing a novel approach and material solution for the recovery and efficient utilization of precious metal catalysts. Attached Figure Description

[0020] The present invention will be further described below with reference to the accompanying drawings and embodiments.

[0021] Figure 1 The X-ray diffraction (XRD) comparison patterns of the ZnAl-LDHs@ZrO2 material prepared in Example 1 of this invention and pure ZrO2 are shown. (a) is the XRD pattern of ZrO2, and (b) is the XRD pattern of ZnAl-LDHs@ZrO2. The horizontal axis is 2θ, in degrees; the vertical axis is the relative intensity.

[0022] Figure 2 This is a high-resolution transmission electron microscope (HRTEM) image of the ZnAl-LDHs@ZrO2 material prepared in Example 1 of this invention.

[0023] Figure 3 This is a schematic diagram of the catalyst sedimentation experimental equipment and its experimental process used in the test examples of this invention. Detailed Implementation

[0024] The following will be combined with the appendix Figure 1-3 The technical solution of the present invention will be clearly and completely described in detail with specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products. Example 1

[0025] A laboratory-scale preparation method for layered zinc-aluminum composite hydroxide-modified zirconium oxide with a low zinc-to-aluminum ratio, namely ZnAl-LDHs@ZrO2 (low ZnAl ratio), wherein the modification amount of ZnAl-LDHs is based on 1 / 200 of the mass of ZrO2 and the ZnAl ratio is 4:1.

[0026] The preparation method is as follows: S1: Preparation of ZnAl-LDHs colloid (low ZnAl ratio): According to Zn 2+ ions / Al 3+Weigh out the corresponding Zn and Al salts in a 4:1 ratio and dissolve them in deionized water, denoted as solution A; dissolve sodium hydroxide in deionized water, denoted as solution B; dissolve sodium carbonate in deionized water, denoted as solution C; slowly add solutions A and B dropwise to a three-necked flask containing solution C at room temperature, stirring vigorously and controlling the pH to 9.0 ± 0.1. After the addition of solution A is complete, stop adding solution B. Under gentle stirring, heat the resulting colloid at 60°C. o ZnAl-LDHs colloids can be obtained by aging at C for 6 h.

[0027] Among them, Zn 2+ Ions, Al 3+ The total molar mass of ions is in the ratio of 1:3 to the molar mass of sodium hydroxide and 6:1 to the molar mass of sodium carbonate; the molar concentration of solution B is 0.05 mol / L and the molar concentration of solution C is 0.01 mol / L.

[0028] S2: Small-scale preparation of ZnAl-LDHs@ZrO2 material (low ZnAl ratio): 12 g of zirconium oxide was added to the ZnAl-LDHs colloid and stirred vigorously for 3 h to allow ZnAl-LDHs and ZrO2 to be fully adsorbed and self-assembled. The resulting white precipitate was filtered, washed several times with deionized water, and dried to obtain ZnAl-LDHs@ZrO2 material. Under these conditions, the mass ratio of ZnAl-LDHs / ZrO2 was 1:200.

[0029] like Figure 1 As shown, (a) is the XRD pattern of commercially available ZrO2, and (b) is the XRD pattern of ZnAl-LDHs@ZrO2 synthesized in Example 1 of this invention. A JCPDS XRD standard card is attached at the bottom of the image for reference. It can be seen from the figures that the XRD pattern at a 2θ angle of 11.6°... o 23.4 o 34.6 o 39.2 o 46.6 o 60.1 o and 61.5 oCharacteristic diffraction peaks of ZnAl-LDHs (003), (006), (012), (015), (018), (110), and (113) were clearly observed (some of which overlapped with the diffraction peaks of ZrO2). All other peaks were characteristic XRD diffraction peaks of monoclinic ZrO2, indicating the synthesis of a well-structured ZnAl-LDHs@ZrO2 composite material. In Figure (b), the diffraction angle of the first strong peak (003) of ZnAl-LDHs is 10–15 degrees, and the diffraction angle of the second strong peak (006) is 20–25 degrees. The height ratio of the first to the second strong peak is (1–3):1.

[0030] like Figure 2 As shown, Figure 2 The image shows an HRTEM image of ZnAl-LDHs@ZrO2 synthesized in Example 1 of this invention. The area enclosed by the yellow dashed line in the image represents the sheet-like ZnAl-LDHs formed on ZrO2 through electrostatic self-assembly, indicating the formation of a ZnAl-LDHs@ZrO2 structure. Example 2

[0031] A pilot-scale laboratory preparation method for layered zinc-aluminum composite hydroxide-modified zirconium oxide with a low zinc-to-aluminum ratio, namely ZnAl-LDHs@ZrO2 (low ZnAl ratio), wherein the modification amount of ZnAl-LDHs is based on 1 / 200 of the mass of ZrO2 and the ZnAl ratio is 4:1.

[0032] The preparation method is as follows: S1: Preparation of ZnAl-LDHs colloid (low ZnAl ratio): According to Zn 2+ ions / Al 3+ A solution A is prepared by dissolving the corresponding Zn and Al salts in deionized water at a ratio of 4:1 (ions = 1). Sodium hydroxide is dissolved in deionized water and denoted as solution B. Sodium carbonate is dissolved in deionized water and denoted as solution C. Solutions A and B are slowly added dropwise to a 200 L glass reactor containing solution C at room temperature, with vigorous stirring and pH controlled at 8.5 ± 0.5. After the addition of solution A is complete, the addition of solution B is stopped. The resulting colloid is then heated at 60 °C with gentle stirring. o ZnAl-LDHs colloids can be obtained by aging at C for 6 h.

[0033] Among them, Zn 2+ Ions, Al 3+ The total molar mass of ions is in the ratio of 1:3 to the molar mass of sodium hydroxide and 6:1 to the molar mass of sodium carbonate; the molar concentration of solution B is 0.05 mol / L and the molar concentration of solution C is 0.01 mol / L.

[0034] S2: Pilot-scale preparation of ZnAl-LDHs@ZrO2 materials (low ZnAl ratio): 1.2 kg of zirconium oxide was added to the above ZnAl-LDHs colloid, and the mixture was stirred vigorously for 3 h to allow ZnAl-LDHs and ZrO2 to fully adsorb and self-assemble. The resulting white precipitate was filtered, washed several times with deionized water, and dried to obtain ZnAl-LDHs@ZrO2 material. Under these conditions, the ZnAl-LDHs / ZrO2 mass ratio was 1:200. The feed amount for the pilot-scale preparation of the colloid was 100 times that of the small-scale preparation. Example 3

[0035] A pilot-scale laboratory preparation method for layered zinc-aluminum composite hydroxide-modified zirconium oxide with a high zinc-to-aluminum ratio, namely ZnAl-LDHs@ZrO2 (high ZnAl ratio), wherein the modification amount of ZnAl-LDHs is based on 1 / 200 of the mass of ZrO2, and the ZnAl ratio is 12:1. The preparation method is as follows: S1: Preparation of ZnAl-LDHs colloid (high ZnAl ratio): According to Zn 2+ ions / Al 3+ A solution A is prepared by dissolving the corresponding Zn and Al salts in deionized water at a ratio of 12:1 (ions = 12:1). Sodium hydroxide is dissolved in deionized water and denoted as solution B. Sodium carbonate is dissolved in deionized water and denoted as solution C. Solutions A and B are slowly added dropwise to a three-necked flask containing solution C at room temperature, with vigorous stirring and the pH controlled at 9.0 ± 0.1. After the addition of solution A is complete, the addition of solution B is stopped. The resulting colloid is then heated at 60°C with gentle stirring. o ZnAl-LDHs colloids can be obtained by aging at C for 6 h.

[0036] Among them, Zn 2+ Ions, Al 3+ The total molar mass of ions is in the ratio of 1:3 to the molar mass of sodium hydroxide and 6:1 to the molar mass of sodium carbonate; the molar concentration of solution B is 0.05 mol / L and the molar concentration of solution C is 0.01 mol / L.

[0037] S2: Small-scale preparation of ZnAl-LDHs@ZrO2 material (high ZnAl ratio): 12 g of zirconium oxide was added to the ZnAl-LDHs colloid and stirred vigorously for 3 h to allow ZnAl-LDHs and ZrO2 to be fully adsorbed and self-assembled. The resulting white precipitate was filtered, washed several times with deionized water, and dried to obtain ZnAl-LDHs@ZrO2 material. Under these conditions, the mass ratio of ZnAl-LDHs / ZrO2 was 1:200. Comparative Example 1

[0038] A laboratory-scale preparation method for zinc hydroxide-modified zirconium oxide, namely Zn(OH)₂@ZrO₂, wherein the modification amount of Zn(OH)₂ is based on 1 / 200 of the mass of ZrO₂, and the preparation method is as follows: Step A: Preparation of Zn(OH)2 solid suspension: Weigh out the corresponding Zn salt and dissolve it in deionized water. Add sodium hydroxide of twice the molar concentration to obtain a flocculent precipitate. Under gentle stirring, heat the resulting flocculent precipitate at 60°C. o Aging at C for 6 h yields a Zn(OH)2 solid suspension.

[0039] Step B: Small-scale preparation of Zn(OH)2@ZrO2 material.

[0040] 12 g of zirconium oxide was added to the Zn(OH)2 solid suspension and stirred vigorously for 3 h to form a solid mixture of Zn(OH)2 and ZrO2. The resulting white precipitate was filtered, washed several times with deionized water, and dried to obtain Zn(OH)2@ZrO2 material. Under these conditions, the mass ratio of Zn(OH)2 / ZrO2 was 1:200. Comparative Example 2

[0041] A method for preparing zirconium oxide, ZrO2, by hydrothermal treatment is as follows: Step A: Take 12 g of commercially available ZrO2 and fully disperse it in deionized water to form a suspension. Under gentle stirring, heat the ZrO2 suspension at 60°C. o After aging at C for 6 h, the resulting white precipitate was filtered, washed several times with deionized water, and dried to obtain hydrothermally treated ZrO2. Test case

[0042] The sedimentation performance (benzene partial hydrogenation reaction performance, Ru loss rate, and carbon balance) of the materials from Examples 1-3 and Comparative Examples 1-2 were tested, and the experimental results are summarized in Table 1. The methods are as follows: First, add approximately 200 mL of the catalyst and reaction solution mixture after partial hydrogenation of benzene to the catalyst settling device. Before starting the catalyst settling timer, set the mechanical stirring speed to 300-400 rpm and stir for 90 seconds to ensure the catalyst and reaction solution are evenly mixed. Stop stirring and start timing. Record the drop in liquid level and the height of the organic phase at regular intervals, and calculate the proportion of clarified organic phase to the total organic phase (refer to...). Figure 3 (As shown).

[0043] After a 300-second timeout, the solid phase of the aqueous phase was collected to measure the rate of Ru loss.

[0044] The calculation process for Ru loss rate is as follows: First, measure the mass m1 of Ru added in the laboratory pilot experiment; then, collect the catalyst solid in the aqueous phase through the lower outlet of the liquid-liquid separator and measure the mass m2 of Ru therein; Ru loss rate η / % = (m1-m2) / m1 × 100% (simultaneously collect and measure the mass m3 of catalyst solid in the "oil-water interface, emulsion layer, and oil phase" using ICP to confirm the accuracy of the results). The calculation process for the catalyst settling rate is as follows: by measuring the volume of the catalyst layer that has descended. V cat Settling time t min quality of catalyst g cat , Calculate the settling rate of the catalyst ν = V cat / ( t min ·g cat ).

[0045] Table 1. Catalytic performance evaluation results of Examples 1-3 and Comparative Examples 1-2

[0046] As can be seen from the data in Table 1, the ZnAl-LDHs@ZrO2 (low ZnAl ratio) prepared by combining the colloidal method and electrostatic self-assembly method in Example 1 did not reduce the reaction performance of the partial hydrogenation of benzene to cyclohexene (benzene conversion rate slightly greater than 40%, cyclohexene selectivity about 80%), while promoting the sedimentation of the noble metal Ru nanoparticles. The Ru loss rate was only 1.4%, and the catalyst sedimentation rate was moderate, making it the best choice.

[0047] Although the Ru loss rate was also 1.4% in Example 3, the reaction activity of the partial hydrogenation of benzene to cyclohexene was slightly reduced. This shows that a faster catalyst settling rate is not necessarily better. This is because the partial hydrogenation of benzene to cyclohexene is a multiphase reaction system containing four phases: hydrogen, organic benzene, inorganic zinc sulfate solution, and solid catalyst. If the settling rate of the solid catalyst is too fast, the contact frequency between the solid catalyst and benzene will decrease, thereby reducing the catalytic activity. Experimental data indicate that a suitable catalyst settling rate should be controlled between 6 and 8%. cm 3 / ( min · g cat )between.

[0048] In Comparative Example 1, Zn(OH)2@ZrO2, as a dispersant, reduced the reactivity of the partial hydrogenation of benzene to cyclohexene, with a Ru loss rate as high as 9.8%. In Comparative Example 2, unmodified ZrO2, as a dispersant, also reduced the reactivity of the partial hydrogenation of benzene to cyclohexene, with a Ru loss rate as high as 7.7%.

[0049] Data from Examples 1 and 2, and Comparative Examples 1 and 2, show that ZnAl-LDHs@ZrO2 (low ZnAl ratio) is more suitable for the partial hydrogenation reaction system of benzene than Zn(OH)2@ZrO2 and unmodified ZrO2. This is because the ZnAl-LDHs modified on the ZrO2 surface has a typical layered structure, with its main layers carrying a positive charge and rich in hydroxyl groups. Through electrostatic attraction and coordination with surface hydroxyl groups, it can efficiently adsorb Ru nanoparticles, effectively suppressing Ru loss. In contrast, pure Zn(OH)2 is nearly electroneutrally neutral, and its electrostatic adsorption of Ru nanoparticles is weak, making it difficult to effectively suppress Ru loss. Replacing ZrO2 with ZnAl-LDHs@ZrO2 can increase the catalyst settling rate while reducing Ru loss during the settling process by approximately 5% to 6%.

[0050] While specific embodiments of the present invention have been described above, those skilled in the art should understand that the specific embodiments described are merely illustrative and not intended to limit the scope of the present invention. Equivalent modifications and variations made by those skilled in the art in accordance with the spirit of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A layered composite hydroxide-modified zirconium oxide material, characterized in that: The material is composed of a layered composite hydroxide and zirconium oxide; the layers of the layered composite hydroxide are composed of divalent metal cations and trivalent metal cations, and the layers are positively charged; the divalent metal cations are selected from at least one of Zn²⁺, Mg²⁺, Co²⁺, Ni²⁺, and Cu²⁺, and the trivalent metal cations are selected from at least one of Al³⁺, Fe³⁺, Co³⁺, Mn³⁺, and Ga³⁺; the modification amount of the layered composite hydroxide is 1 / 30 to 1 / 200 of the mass of zirconium oxide.

2. The layered composite hydroxide-modified zirconium oxide material according to claim 1, characterized in that: In the layered composite hydroxide, the molar ratio of divalent metal cations to trivalent metal cations is (2~16):

1.

3. The layered composite hydroxide-modified zirconium oxide material according to claim 1, characterized in that: The layered composite hydroxide is a zinc-aluminum composite hydroxide (ZnAl-LDHs), and the zirconium oxide is a monoclinic zirconium oxide (ZrO2).

4. The layered composite hydroxide-modified zirconium oxide material according to claim 1, characterized in that: The material has a first strong diffraction peak on the (003) crystal plane of the layered composite hydroxide at a 2θ angle of 10-15 degrees, and a second strong diffraction peak on the (006) crystal plane at a 2θ angle of 20-25 degrees, and the height ratio of the first strong peak to the second strong peak is (1-3):

1.

5. A method for preparing a layered composite hydroxide-modified zirconium oxide material as described in any one of claims 1-4, characterized in that: Includes the following steps: S1. Preparation of layered composite hydroxide colloid: According to the molar ratio of divalent metal ions to trivalent metal ions of (2~16):1, weigh the corresponding divalent metal salts and trivalent metal salts and dissolve them in deionized water to prepare solution A; dissolve sodium hydroxide in deionized water to prepare solution B; dissolve sodium carbonate in deionized water to prepare solution C; under stirring conditions, slowly add solutions A and B dropwise to the reactor containing solution C, and control the pH of the system to 8.0±2.

0. After solution A has been added, stop adding solution B. Then age the resulting colloid at 40°C to 90°C for 3 to 12 hours to obtain a layered composite hydroxide colloid. S2. Preparation of layered composite hydroxide-modified zirconia materials: Zirconia is added to the layered composite hydroxide colloid obtained in step S1, and the mixture is stirred vigorously for 3 to 12 hours to allow it to fully adsorb and self-assemble. The resulting precipitate is filtered, washed, and dried to obtain the layered composite hydroxide modified zirconium oxide material.

6. The preparation method according to claim 5, characterized in that: In step S1, the ratio of the total molar amount of the divalent and trivalent metal ions to the molar amount of sodium hydroxide is 1:(1~5); the molar concentration of solution B is 0.01~0.1 mol / L.

7. The preparation method according to claim 5, characterized in that: In step S1, the ratio of the total molar amount of divalent and trivalent metal ions to the molar amount of sodium carbonate is (2~16):1; the molar concentration of solution C is 0.01~0.1 mol / L.

8. The preparation method according to claim 5, characterized in that: In step S2, the amount of zirconium oxide added is 30 to 200 times the amount of layered composite hydroxide modification, and the resulting precipitate is dried at 40°C to 80°C for 4 to 16 hours.

9. The application of a layered composite hydroxide-modified zirconium oxide material as described in any one of claims 1-4 in a benzene-to-cyclohexene partial hydrogenation reaction system, characterized in that: The material is used as a catalyst dispersant, and the amount of dispersant is 5 to 10 times that of the catalyst, in order to promote the sedimentation of noble metal Ru nanoparticles in the reaction system and reduce Ru loss.

10. The application according to claim 9, characterized in that: The application includes using the layered composite hydroxide-modified zirconium oxide material together with a Ru catalyst for the partial hydrogenation of benzene to cyclohexene, with a sedimentation rate of 6~8 cm³ / (min·gcat) for the catalyst system.